Diagnosing the difficulties of school textbook content at the primary education stage from the perspective of primary school teachers: a field study in some educational districts of the Wilaya of M’sila - saoudi, Ahmed; nouasri, zohra (El Omda in Linguistics and Discourse Analysis, 2025)
The current study aimed at, diagnosing, the content difficulties of school books, in the primary education stage from the point of view of teachers, in some provinces of the state of M'sila. This content was prepared by researchers. On a sample of professors in some provinces of M'sila Province. The study reached the following results: - There is a difficulty in the content of primary school books from the point of view of primary education teachers. - There are not differences between, the sexes in diagnosing the difficulties of the content of primary education textbooks, except after implementing and evaluating the content, where there were statistically significant differences in favor of males. - There are no statistically significant differences in diagnosing the difficulties of the content of primary education school books. due to the nature of the education of the primary education teacher.